Night Shift Work and Levels of 6-Sulfatoxymelatonin and Cortisol in Men - Mirick, Dana K.; Bhatti, Parveen; Chen, Chu; Nordt, Frank; Stanczyk, Frank Z.; Davis, Scott (Cancer epidemiology, biomarkers & prevention, 2013)
Background: Night shift work is associated with cancer among men, but the biologic mechanism is unclear. We investigated whether male night shift workers showed changes in levels of melatonin and cortisol, potential biomarkers of cancer risk. Methods: Urine was collected from 185 night shift and 158 day shift-working male healthcare providers, aged 22 to 55 years, throughout work and sleep periods, and assayed for 6-sulfatoxymelatonin and cortisol. Morning serum was collected within 90 minutes of completing the night and assayed for cortisol. Results: Night shift workers had significantly lower 6-sulfatoxymelatonin levels during daytime sleep, nighttime work, and nighttime sleep on off-nights (57%, 62%, and 40% lower, respectively), relative to the day shift workers during nighttime sleep (P < 0.0001); urinary cortisol in night shift workers was 16% higher during daytime sleep and 13% lower during nighttime sleep on off-nights (P < 0.05). Morning serum cortisol post-work and post-sleep in night shift workers were 24% and 43% lower, respectively, than post-sleep levels among day shift workers (P < 0.0001). Within-subject comparisons among the night shift workers revealed significantly lower melatonin levels and significantly higher urinary cortisol levels during daytime sleep and nighttime work, relative to nighttime sleep (P < 0.01); morning serum cortisol levels post-work were lower than those post-sleep. Conclusions: Night shift workers have substantially lower 6-sulfatoxymelatonin during night work and daytime sleep, and levels remain low when night shift workers sleep at night. Chronic reduction in melatonin among night shift workers may be an important carcinogenic mechanism. Cortisol secretion patterns may be impacted by night shift work, which could affect cancer risk. Impact: Shift work could be an important risk factor for many types of cancer. Cancer Epidemiol Biomarkers Prev; 22(6); 1079–87. ©2013 AACR.